The Possession Degree of E-Learning Teaching Strategies by Female Teachers of the First Three Grades and their Attitudes towards it from their Point of View - Alwama, Hussein Ali Mohammed; Albdour, Ameen (Dirasat: Educational Sciences, 2023)
Objectives: This study aimed to determine the degree to which female teachers of the first three grades possess e-learning teaching strategies and explore their attitudes towards it from their point of view. Methods: The study employed a descriptive survey method. The sample consisted of 160 female teachers from the first three grades in Ma'an Governorate, Jordan. The sample was selected using a stratified random method. To achieve the study objectives, two tools were utilized: a questionnaire consisting of 18 items to measure the teachers' possession of e-learning-based teaching strategies, and a measure of attitudes towards e-learning, comprising 16 items. Results: The study's findings revealed a high degree of possession of e-learning teaching strategies and positive attitudes towards e-learning among teachers of the first three grades in Jordan. Conclusion: Based on the study results, the researcher recommends several suggestions. Firstly, it is recommended to encourage first three-grade teachers to utilize learning management systems such as Teams and Madrasati platforms for collaborative and participatory e-learning through the web. Additionally, there is a need for more training courses and specialized workshops in the field of e-learning utilization.